Assessing Preferences Among Behavioral Interventions With Japanese Parents of Children With Developmental Disabilities. Issue 3 (3rd July 2017) - Kawarai, Sayaka; Symon, Jennifer B. G.; Hernández, Anthony; Fryling, Mitch J.
ABSTRACT: As the cultural dynamic continues to become increasingly complex, it is critical to assess cultural factors that influence practice. The present study considers the treatment preferences of Japanese mothers of children with developmental disabilities. After answering demographic questions, each participant was given four scenarios and asked how they would respond by choosing one of four interventions (differential reinforcement, ignoring, reprimanding, and time-out). Overall, we found that parents preferred differential reinforcement strategies the most. Moreover, parents who reported that their children had a history of involvement with applied behavior analysis were especially likely to choose differential reinforcement. Implications for future research and practice are provided.